MORTALITY, MIGRATION, AND RURAL TRANSFORMATION IN SUB-SAHARAN AFRICA'S URBAN TRANSITION. (6th December 2016) - Fox, Sean
Abstract: The stylized facts of Africa's urban transition highlight the limitations of traditional economic models of urbanization. Recent research has provided evidence that demographic rather than economic processes provide a more compelling explanation for observed trends in the region. In particular, mortality decline appears to be both a necessary and sufficient condition for urbanization to occur and a key driver of urban growth more broadly. The accumulation of survey data over the past few decades and the development of new geospatial datasets that incorporate satellite imagery are facilitating new, more spatially nuanced insights into the dynamics of urban population change in the region. This offers opportunity to develop better policies for managing urban change than those adopted in the past, which placed a misguided emphasis on manipulating migration incentives with little evidence of positive benefits.